2002
DOI: 10.1046/j.1471-4159.2002.00928.x
|View full text |Cite
|
Sign up to set email alerts
|

Microglial activation‐mediated delayed and progressive degeneration of rat nigral dopaminergic neurons: relevance to Parkinson's disease

Abstract: The etiology of sporadic Parkinson's disease (PD) remains unknown. Increasing evidence has suggested a role for inflammation in the brain in the pathogenesis of PD. However, it has not been clearly demonstrated whether microglial activation, the most integral part of the brain inflammatory process, will result in a delayed and progressive degeneration of dopaminergic neurons in substantia nigra, a hallmark of PD. We report here that chronic infusion of an inflammagen lipopolysaccharide at 5 ng/h for 2 weeks in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
496
2
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 640 publications
(526 citation statements)
references
References 54 publications
16
496
2
6
Order By: Relevance
“…In addition to oxidative stress also other mechanisms have been proposed to be involved in selective DA neuron degeneration in PD, including excitotoxicity, intracellular calcium and metal ion rise, neurofibrillary tangle formation and disruption of the cytoskeletal transport [112]. More recently, neuroinflammation and microglial activation have been implicated in the neurodegenerative process in PD, as initially suggested by McGeer et al [155] and then by several authors ( [77,89,95,97,104,102,107,148,168]). In fact, studies accumulated over the last two decades have clearly indicated the presence of an abnormal glial response in postmortem nervous system of PD patients.…”
Section: Parkinson's Disease and Neuroinflammationmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition to oxidative stress also other mechanisms have been proposed to be involved in selective DA neuron degeneration in PD, including excitotoxicity, intracellular calcium and metal ion rise, neurofibrillary tangle formation and disruption of the cytoskeletal transport [112]. More recently, neuroinflammation and microglial activation have been implicated in the neurodegenerative process in PD, as initially suggested by McGeer et al [155] and then by several authors ( [77,89,95,97,104,102,107,148,168]). In fact, studies accumulated over the last two decades have clearly indicated the presence of an abnormal glial response in postmortem nervous system of PD patients.…”
Section: Parkinson's Disease and Neuroinflammationmentioning
confidence: 96%
“…The substantia nigra is reported to be particularly susceptible to LPS-induced injury because it is rich in microglia [120]. LPS induces a rapid activation of microglia and a delayed, progressive and selective destruction of nigral dopaminergic neurons both in vivo and in vitro ( [78,77,79]). Finally, using mice carrying a deletion in the gene coding for NADPH oxidase, one major source of intracellular ROS, or in Mac-1 it has been possible to clearly demonstrate that the production of ROS by LPSactivated microglia is directly toxic to neurons as well as the secretion of proinflammatory molecules, which foster neurodegeneration as well ( [182,190,252,265,264]).…”
Section: Animal Models Of Parkinson's Diseasementioning
confidence: 99%
“…To test this hypothesis, an inflammation-mediated rat model of PD was established in our laboratory by supranigral and continuous infusion of nanogram quantities of an inflammogen (LPS) for 2 weeks (Gao et al, 2002b). Maximal activation of microglia in the SN occurred between 1 to 2 weeks after the start of LPS infusion.…”
Section: Inflammogen-induced Microglial Activation and Dopaminergic Nmentioning
confidence: 99%
“…First, neurodegeneration induced by a single bolus application of microgram levels of LPS occurred within a few days (Castano et al, 1998;Liu et al, 2000d;Lu et al, 2000;Iravani et al, 2002). In contrast, neurodegeneration induced by chronic infusion of nanogram levels of LPS progressed over weeks (Gao et al, 2002b). Second, in the acute model, neurodegeneration was not limited to nigral dopaminergic neurons because other neurons such as ␥-aminobutyric acid-containing neurons were also damaged.…”
Section: Inflammogen-induced Microglial Activation and Dopaminergic Nmentioning
confidence: 99%
“…Postmortem CSF and brain tissue from PD patients have elevated TNF and IFN- levels [118,119]. Rodent models of chronic LPS infusion lead to brain inflammation with subsequent delay and selective degeneration of dopaminergic neurons [120]. Peripheral LPS administration resulted in TNF production, which crosses the blood brain barrier via TNF receptors, leading to neuroinflammation [121,122].…”
Section: Proteotoxic Stress In the Pathogenesis Of Diseases Not Formementioning
confidence: 99%